Assessment of Color Stability of Bleached Enamel Surface After The Application Of Some Natural Antioxidants For Different Times - M. Jasim, Haitham; Aljubori, Sawsan H. (Journal of Neonatal Surgery, 2025)
Background: Residual free radicals following bleaching may disrupt adhesion processes, necessitating the application of antioxidants to neutralize these radicals. Nonetheless, concerns persist about the potential for antioxidants to change the color of bleached enamel. Objective: To assess the effect of two natural antioxidants, Moringa oleifera and Salvadora persica, applied at varying time intervals (10, 15, and 20 minutes) on the color of bleached enamel. Methods: Seventy-two non-carious human premolars extracted for orthodontic reasons were chosen. The crowns were sectioned, embedded in acrylic resin, and polished to provide a consistent enamel surface. All samples were subjected to bleaching with 40% hydrogen peroxide gel and subsequently categorized into six experimental groups according to the type of antioxidant (Moringa oleifera or Salvadora persica) and application duration (10, 15, or 20 minutes). Color measurements were conducted prior to and after to the application of antioxidants utilizing a digital colorimeter based in the CIELAB system. Results: Statistical analysis indicated no significant color changes (ΔE) in any of the groups post-antioxidant administration, with all ΔE values remaining beneath the clinically visible threshold. The antioxidant type and treatment duration did not have a statistically significant effect on enamel color (p>0.05). Conclusion: The application of Moringa oleifera and Salvadora persica as post-bleaching antioxidants does not affect the color of bleached enamel. These results validate that natural antioxidants can be utilized post-bleaching without compromising cosmetic results.